The Effect of Giving Ajwa Dates on Increasing Hemoglobin Levels in Adolescent Girls - Romauli, Suryati; Fitriana Iriyani, Nur; Ivanna Kalo, Greaceline Vira (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Anemia is still a nutritional problem especially for adolescent girls. This is because there are still many young women who do not make efforts to prevent anemia. This study aims to determine the effect of giving ajwa dates on increasing Haemoglobin levels in adolescent girls. Method: The design of this study is pre-experimental with a two-group pre-post test design.  A sample of 48 respondents. Data were obtained through examination of Haemoglobin levels before and after the intervention. The data was analyzed based on a data normality test. Results: The Hb levels of adolescent girls in the intervention group before being given ajwa dates had an average value of 9.463, std. deviation of 1.3276 with the lowest Hb of 5.1 gr/dl and the highest Hb of 10.9 gr/dl, while the control group had an average value of 11.667, std. deviation of .3046 with the lowest Hb of 11.0 gr/dl and the highest Hb of 12.2 gr/dl. The hemoglobin levels of adolescent girls in the intervention group after being given ajwa dates had an average value of 10.829, std. deviation of 1.3917 with the lowest Hb of 7.7 gr/dl and the highest Hb of 13.5 gr/dl, while in the control group had an average value  of 11.221, std. deviation of .5365 with the lowest Hb of 10.0 gr/dl and the highest Hb of 12.2 gr/dl.  There is an effect  of giving ajwa dates on increasing haemoglobin levels in adolescent girls with a value of p = 0.001